РОЗВИТОК ПРАВОВОГО РЕГУЛЮВАННЯ ВИКОРИСТАННЯ ПРИРОДНИХ РЕСУРСІВ У ГОСПОДАРСЬКІЙ ДІЯЛЬНОСТІ В УКРАЇНІ - Riabtsova, А.H. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2021)
The formation and development of legal regulation of the use of natural resources in economic activity is analyzed. It is established that certain aspects of the legal regulation of the use of some natural resources can be found in Ruska Pravda, which was carried out mainly for tax purposes. The development of legislation on the use of natural resources in the Middle Ages and during the stay of Ukraine as part of the Russian Empire is analyzed. It is established that the use of natural resources on Ukrainian lands during their stay in the Polish-Lithuanian principality was regulated mainly by customary law. Agrarian reform was carried out as a result of the adoption of the act “Ustav na Voloky” (1557). In addition, in 1567 the Forest Charter was adopted, which was one of the first acts in Europe in the field of forest protection and use. It is substantiated that until the twentieth century there was a rather fragmentary regulation of the protection and preservation of natural resources, mainly with a view to protecting the ownership of certain natural objects, especially land. The regulation of the use of natural resources in economic activity in the Soviet period and after the declaration of independence is studied. Among the first acts adopted after the revolution was the “Decree on Land” of November 8, 1917, according to which the land became state property. However, only since the 60 of the last century special laws have been adopted aimed at legal protection of nature. Normative-legal acts of independent Ukraine from the standpoint of regulating the use of natural resources in eco- no mic activity are systematized into three groups: normative acts regulating economic activity in general and certain aspects of natural resources protection; regulations that mainly regulate the protection of natural resources in general and estab lish certain principles of their use in economic activities; regulations governing the protection and use of certain types of natural resources, including in economic activities. In addition, the periodization of the historical development of legislative regulation of the use of natural resources in economic activity is suggested. REFERENCES